Weather and crime: Cautious evidence from South Africa - Mirjam Anna Brüderle; Jörg Peters; Gareth Roberts (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
South Africa has one of the highest crime rates in the world. This paper examines the effect of weather shocks on various types of crime. Using a 12-year panel data set at monthly resolution on the police ward level, we observe a short-term effect of temperatures on violent crime, supporting the heat-aggression link suggested by psychological research. Furthermore, we find evidence for a subtle medium-term effect of weather on crime via droughts and agricultural income, which is in line with the economic theory of crime. Yet, we also emphasize often neglected but well-documented limitations to the interpretability of weather data and weather-induced mechanisms. Recognizing these limitations, we conclude with a cautious interpretation of our findings to inform police deployment strategies.
Keywords: C33; O55; Q54; R11; 330; South Africa; weather; crime; income shocks